2016
DOI: 10.1007/s00190-016-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic impact assessment of GRACE error correlation on data assimilation in hydrological models

Abstract: We use GRACE data to improve a hydrological model estimations • Data assimilation is used to ingrate observation into a model • We apply stochastic and deterministic ensemble-based Kalman filters (EnKF) and Particle filter • Filters performances are compared to reach the best result

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 108 publications
(97 reference statements)
2
69
0
Order By: Relevance
“…5.4), which is important for hydrological assessments (see e.g. Schumacher et al 2016). The spatial coverage of the current contribution also extends the previous studies to cover the entire Iran and the Tigris-Euphrates river basin.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…5.4), which is important for hydrological assessments (see e.g. Schumacher et al 2016). The spatial coverage of the current contribution also extends the previous studies to cover the entire Iran and the Tigris-Euphrates river basin.…”
Section: Introductionsupporting
confidence: 70%
“…The zonal degree 2 spherical harmonic coefficients ðC 20 Þ are replaced by those in Cheng et al (2013) (see also http://grace.jpl.nasa.gov) since they are found to be better estimated. GRACE Level 2 products contain correlated errors (due to measurement errors, sampling of the mission, and background errors, see, e.g., Schumacher et al 2016), which express themselves as striping patterns in the spatial domain. These errors mask hydrological signals and make their detection difficult (Kusche 2007).…”
Section: Total Water Storage Products From Gracementioning
confidence: 99%
See 1 more Smart Citation
“…The GRACE mission has also provided novel opportunities to diagnose and to identify systematic deficiencies in global hydrological and land surface models (LSMs) [Swenson and Milly, 2006;Güntner, 2008]. More recently, GRACE observations have been used to improve LSMs, either through changes in model structure and parametrization [Lo et al, 2010;Werth and Güntner, 2010;Swenson and Lawrence, 2015] or directly by means of data assimilation techniques [Zaitchik et al, 2008;Eicker et al, 2014;Kumar et al, 2016;Schumacher et al, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial disaggregation is also needed to reconcile the difference in horizontal resolution between the observations and the model. Recent studies by Eicker et al (2014) and Schumacher et al (2016) suggested including the GRACE variance-covariance error information in the spatial disaggregation step. Both studies proposed using 500 km GRACE spatial resolution to mitigate the ill-posedness of the error covariance matrices in the spatial domain.…”
Section: Introductionmentioning
confidence: 99%